Neutron star cooling in transiently accreting low mass binaries: a new tool for probing nuclear matter - Possenti, A; Colpi, M; Page, D; Geppert, U (2001)
We explore, using an exact cooling code, the thermal evolution of a neutron star undergoing episodes of intense accretion, alternated by long periods of quiescence (e.g. soft X-ray transients; SXRTs here-on). We find that the soft component of the quiescent luminosity of Aql X-1, 4U 1608-522 and of SAX J1808.4-3658 can be understood as thermal emission from a cooling neutron star with negligible neutrino emission. In the case of Cen X-4 strong neutrino emission from the inner core is necessary to explain the observation: this may indicate that the neutron star of Cen X-4 is heavier than 1.4 Mcircle dot. This study opens the possibility of using the quiescent emission of SXRTs as a tool for probing the core superfluidity in relation to the mass of the neutron star.